Correlação da resistência à insulina, circunferência da cintura, e índice de massa corporal com a pressão arterial de adolescentes - Morais, Polyana Resende Silva de (2015)
Introduction: Among the major risk factors for cardiovascular diseases are high blood pressure (hypertension), obesity and insulin resistance (IR). Studies show that blood pressure (BP) increases progressively with an increase of the body mass index (BMI) and in individuals with increased waist circumference (WC), they have a higher risk of developing hypertension, IR and other metabolic disorders since childhood. Objective: To evaluate the correlation between RI, WC and BMI in adolescents with altered levels of PA. Methods: Cross-sectional study with a representative sample of 1025 adolescents aged 12 to 17 years enrolled in public and private schools in a large city. Two groups were evaluated, one formed by the PA that had changed the assessment by casual measurement and / or Home Blood Pressure Measurement (HBPM) and another group formed by those with normal BP. Evaluated anthropometric indicators for BMI and WC calculation. Classified as abnormal blood pressure those with BP percentile> 90 on casual measurement and / or HBPM. Measured fasting plasma glucose and plasma insulin using the HOMA-IR index as indicative of RI. Results: We studied 162 adolescents (35 normal BP group and 127 of the amended BP group) and 61.1% (n = 99) boys, mean age 14.9 ± 1.62 years. Observed 38 children (23.5%) with abnormal HOMA-IR index. Teenagers with altered BP had significantly higher mean values of WC, BMI and HOMA-IR (p <0.05). The WC was higher in boys in both groups (p <0.05), and only changed the BP group was observed HOMA-IR values higher among girls (p <0.05). The correlation between BMI and HOMA-IR in altered pressure group, was moderate and significant (ρ = 0.394; p <0.001), higher than that found in the normal pressure group. The correlation between WC and HOMA-IR was also significant and moderate and similar in both groups (ρ = 0.345; p = <0.05). In HOMA-IR logistic regression analysis was predictor of change in BP (OR = 2.0 / p = 0.001).Conclusion: There is a significant association between RI and PA with impact since childhood. The correlation and association between cardiovascular risks markers observed stronger in the amended BP group suggests that primary prevention measures such risk factors should be implemented early.